Occupational traumatic injuries among offshore seafood processors in Alaska, 2010–2015. (September 2018) - Syron, Laura N.; Lucas, Devin L.; Bovbjerg, Viktor E.; Case, Samantha; Kincl, Laurel
Abstract: Introduction: The U.S. Coast Guard and Federal Occupational Safety and Health Administration have identified the Alaskan offshore seafood processing industry as high-risk. This study used Coast Guard injury reports to describe patterns of traumatic injury among offshore seafood processors, as well as identify modifiable hazards. Methods: From the reports, we manually reviewed and abstracted information on the incident circumstances, injury characteristics and circumstances, and vessel. Traumatic injury cases were coded using the Occupational Injury and Illness Classification System, and a Work Process Classification System. Descriptive statistics characterized worker demographics, injuries, and fleets. Results: One fatal and 304 nonfatal injuries among processors were reported to the Coast Guard during 2010–2015 across multiple fleets of catcher-processor and mothership vessels. The most frequently occurring injuries were: by nature of injury, sprains/strains/tears (75, 25%), contusions (50, 16%), and fractures (45, 15%); by body part affected, upper extremities (121, 40%), and trunk (75, 25%); by event/exposure resulting in injury, contact with objects and equipment (150, 49%), and overexertion and bodily reaction (76, 25%); and by source of injury, processing equipment and machinery (85, 28%). The work processes most frequently associated with injuries were: processing seafood on the production line (68, 22%); stacking blocks/bags of frozen product (50, 17%); and repairing/maintaining/cleaning factory equipment (28, 9%). Conclusions: Preventing musculoskeletal injuries, particularly to workers' upper extremities and trunks, is paramount. Some injuries, such as serious back injuries, intracranial injuries, and finger crushing or amputations, had the potential to lead to disability. Practical applications: Safety professionals and researchers can use the study findings to inform future intervention efforts in this industry. Hazard control measures should target: (a) overexertion from lifting and lowering objects and equipment; (b) equipment and boxes falling and striking workers; (c) workers being caught in running machinery during regular operations; and (d) slips, trips, and falls.